Transformasi Konsep Kebahagiaan Sabai Sabai Menjadi Sakinah Perspektif Tasawuf Sebagai Dasar Model Konseling Islami - Nurhayyu Humairoh Amriyadi; Konto Iskandar Dinata (Al-Kindi, 2025)
This study examines the conceptual relationship between the Thai cultural philosophy of sabai sabai and the Sufi concept of sakinah as a foundation for developing a contextual and multicultural Islamic counseling model. The philosophy of sabai sabai reflects a worldview that emphasizes relaxation, acceptance, and resilience in facing life challenges, functioning as a collective coping strategy in Thai society. In contrast, sakinah is understood as spiritual tranquility attained through a deep relationship with God and cultivated through patience, gratitude, contentment, and trust. This research employs a library-based method by reviewing books, scientific articles, and relevant studies to identify intersections between the two concepts. The results show that both share the understanding that inner peace and happiness are not determined by material achievements but by self-regulation and the refinement of inner awareness. The integration of these concepts offers significant potential to enrich Islamic counseling practice with a more reflective, spiritual, and humanistic approach, making it more relevant to the needs of diverse modern societies